(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The aim of this study is to measure the effects of Economic blocs on Foreign Direct Investment for the group UEMOA and CEMAC, to achieve this goal we study the long-term relationship among Foreign Direct Investment inflows as a dependent variable and Intra- trade as an independent variable using econometric methods such as the var model during the period 2000-2021, the experimental results indicate there is a high degree of co-movement between variables, which confirms that Economic blocs have a positive impact on Foreign Direct Investment in the long term only.